Characterization of a secondary contact zone of the Great Tit Parus major and the Japanese Tit P. minor (Aves: Passeriformes) in Far Eastern Siberia with DNA markers - Kvist, Laura; Rytkönen, Seppo (Zootaxa, 2006)
The Great Tit Parus major and the Japanese Tit P. minor meet and hybridize in a secondary contact zone in Far Eastern Amur River Valley. The genetic characteristics of this hybrid zone were studied by nuclear microsatellites and mitochondrial DNA sequences. Patterns of introgression of nuclear markers, mitochondrial markers and phenotypic characters were found to be different. The possible reasons, such as stronger selection against heterogametic females according to Haldane’s rule, lowered hybrid fitness, assortative mating and factors enforcing introgression, like density-dependent pair-formation, are discussed.